15 Park Avenue - Sen, Aparna, 1945-; Sen, Aparna, 1945-; Vohra, Bipin; Dāśagupta, Jyotishka (Shemaroo Video, 2006)
Mrs. Mathur lives in Calcutta with her divorced daughter Anjali and Mithali, who is about 18 years younger than Anjali from her second marriage. Her son Mahesh gets married to Padma and lives separately. Anjali works as a Lecturer in a college. Mithali grows up in this atmosphere with virtually two mothers, she is quiet and introverted. Things change for the better when she goes to college, then to work with Illustrated Weekly, where she meets and falls in love with Joydeep "Jojo" Roy. Jojo proposes marriage, and is told that Mithali is not well, suffers from schizophrenia, has occasional epilepsy attacks, she must be looked after for the rest of her life. Nevertheless, Jojo decides to marry her. Then the unexpected happens when Mithali is gang-raped near the Bihar-Bengal border area where she was sent on an assignment by her employer. This shatters her completely, and changes the lives of her family and her relation with Jojo, who no longer wants to wed her. In the deep recesses of her mind, Mithali has secured a house on 15 Park Avenue, where she lives with her husband, Jojo, five children, and two dogs. Anjali has attempted several times, albeit in vain, to locate this address. Then a married Jojo re-enters Mithali's life, but Mithali is unable to remember him. He feels sorry for her plight and holds himself responsible, so he decides to help her find 15 Park Avenue.